2020
DOI: 10.7759/cureus.10280
|View full text |Cite
|
Sign up to set email alerts
|

The Gut-Brain Axis and Its Role in Depression

Abstract: The gut microbiota in humans communicates to the central nervous system through the gutbrain axis, and this communication functions in a bidirectional manner. The backbone of this axis is via the vagus nerve allowing the communication. Research on the functionality of the gut-brain axis is present; however, analysis of the diversity and stratification of the gut microbiota is in its infancy. Through the exploration of various studies focusing on the role of the gut microbiota and its effects on the efficacy of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 29 publications
0
8
0
4
Order By: Relevance
“…The vagus nerve is the most direct route of communication between the gut and the brain, thus enabling bidirectional communication. The vagus nerve has also been indicated in the etiology of Parkinson’s disease [ 21 ], Alzheimer’s disease [ 22 ], and depression [ 23 ]. What these conditions have in common is that they are influenced by the gut microbiota through their metabolites and immune-modulating activity.…”
Section: Pathways Of Communication Along the Microbiota–gut–brain Axismentioning
confidence: 99%
See 1 more Smart Citation
“…The vagus nerve is the most direct route of communication between the gut and the brain, thus enabling bidirectional communication. The vagus nerve has also been indicated in the etiology of Parkinson’s disease [ 21 ], Alzheimer’s disease [ 22 ], and depression [ 23 ]. What these conditions have in common is that they are influenced by the gut microbiota through their metabolites and immune-modulating activity.…”
Section: Pathways Of Communication Along the Microbiota–gut–brain Axismentioning
confidence: 99%
“…The vagus nerve responds to components produced or induced by the gut microbiota, such as short chain fatty acids (SCFA), endotoxins, peptides, and cytokines [ 20 ]. Furthermore, neurotransmitters such as serotonin produced within the gut influence vagal functionality [ 23 ].…”
Section: Pathways Of Communication Along the Microbiota–gut–brain Axismentioning
confidence: 99%
“…Functional magnetic resonance imaging (MRI) analysis has previously shown that there is a chronic low-level inflammatory condition in many cases of depression. [ 11 ]…”
Section: Gut–brain Axis In Disordermentioning
confidence: 99%
“…Probiotics and gluten-free diet modulate the gut microbiota composition and improve intestinal immune system, resulting in better symptom control. [ 11 ]…”
Section: Gut–brain Axis In Disordermentioning
confidence: 99%
See 1 more Smart Citation